Factors of risk behaviour forms among young people in Serbia: Analysis of individual and contextual risk factors - Stanojević, Dragan; Ljubičić, Milana (Sociološki pregled, 2020)
In this paper we deal with the research of the relation between risk behaviour forms among young people in Serbia and the assumed risk factors. This paper is aimed at using the criminology theory in order to test the effect of environmental factors on more broadly understood risk behaviour of young people. The conceptual framework of the study is founded on the general criminology theory of R. Agnew, while the hypothesis directing our research is: Features of the social environment as well as individual and family characteristics constitute the strain factors pushing a young person into risk behaviour. For the data of the representative study on young people (N=1186) aged between 15 and 29, conducted in 2015, we applied the statistical technique of multilevel modelling which ensures the establishment of relations with risk behaviour forms at individual and contextual levels. The findings of the multilevel analysis indicate that individual and contextual factors are equally important in the understanding of risk behaviour forms. In other words, gender and age, as well as social disorganization and culture of violence constitute a fertile soil for risk occurrence.